1992
DOI: 10.1038/ki.1992.363
|View full text |Cite
|
Sign up to set email alerts
|

Early glycosilation products induce glomerular hyperfiltration in normal rats

Abstract: The effects of early glycosylation products (Amadori Products, AP) were investigated in male Munich-Wistar rats to establish whether AP play a role in the pathogenesis of glomerular hyperfiltration of early diabetic nephropathy. To mimic such a condition, normal rats were transfused with blood containing in vitro glycated serum (Group GLYC) to achieve plasma levels of Amadori products similar to those measured in rats with streptozotocin-induced diabetes. Rats transfused with normal blood were used as control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
2
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 23 publications
0
31
2
1
Order By: Relevance
“…This effect is opposite to that seen after an infusion of glycated albumin (47) and more consistent with changes seen in advanced disease or with severe hyperglycemia (48). Notably, both of these states are associated with high levels of circulating AGE.…”
Section: Discussioncontrasting
confidence: 46%
“…This effect is opposite to that seen after an infusion of glycated albumin (47) and more consistent with changes seen in advanced disease or with severe hyperglycemia (48). Notably, both of these states are associated with high levels of circulating AGE.…”
Section: Discussioncontrasting
confidence: 46%
“…It is not likely that the effects of these agents on GFR can be explained by differences in glycaemic control because none of the treatments influenced plasma glucose, body weight or glycated haemoglobin. Other investigators have reported that early glycation products induce glomerular hyperfiltration [21] but it was difficult to determine how accurately early AGEs had been separated from late AGEs in this study. This indicates that direct effects of AGEs on glomerular filtration cannot be excluded.…”
Section: Discussionmentioning
confidence: 57%
“…For quantitation, sections were coded and read by an observer unaware of the experimental protocol applied. [10][11][12][13][14][15] glomeruli were selected at random in PAS-stained sections from each animal in each experimental group. The extent of increase in mesangial matrix was determined by the presence of PAS-positive material in the mesangial region using a digital planimeter (Southern Microscope Instruments, Inc., Atlanta, GA) and factored by the glomerular tuft area.…”
Section: Methodsmentioning
confidence: 99%
“…This postulate has been strengthened with experimental evidence demonstrating that glycated serum proteins adversely affect renal glomerular capillary function, structure, and metabolism (10)(11)(12)(13). In previous studies, we have shown that human sera containing diabetic concentrations of glycated albumin inhibit the replication of murine mesangial cells in culture and stimulate the production and gene expression of type IV collagen, the principal constituent of the expanded extracellular matrix observed in the diabetic renal glomerulus (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%